Penggandaan Tunas Abaca Melalui Kultur Meristem - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT The study on "Multiplication of Abaca Bud Through Meristem.Culture" has aims to . evaluate the effeCt of combinant concentration of plant growth regulator of BAP. and NAA, and determine the proper combinant concentration to multiplication the abaca bud a- _ in the abca meristem culture. . The study was conducted from October 2002. to April 200.3 according to Randomized treatment is made up by two factors. The first factor is concentration of BAPconsisting,of four levels, those are 0 M (Bo), 10-7 M (B7), le M (Bd and _IV M (B5): The second factor is concentration of NAA, consisting of three levels, i.e., .0 M (No), 10-7M (N7), and The result of the study proves that the combination of BAP:and NAA gives a significant effect to the parameter of buds number, buds length and number of leaves in subculture I and subculture IL The treatment of B5N7 results in the highest of buds number or in the number oilcans, i.e., 5.07 and 6.00 in sub culture Land 4.37 and 6.25 in sub culture 1I, respectively. Key words: Abaca, Meristem, BAP, NAA. . â¢ INTISARI Penelitian "Penggandaan Tunas Abaci Melalui 'Kultur Meristem" bettujuan .untuk mengevaluasi pengaruh kombinasi zat pengatur tumbuh BAP dan-NAA Seth menentukan konsentrasi kombinasi zat pengatur tumbuh- tersebut yang tepat untuk periggandaan' tunas pada kultur meristem abaca. Penelitian dilaksanakan mulai bulan Oktober 2002 hingga bulanMaret 2003.. Rancangan Acak Kelompok digunakan untuk mengatur perlakudn dengan tiga' ulangan Perlakuan terdiri dari dua faktor, faktor pertama adalah k_ BAP .yang terdi0 dari 4 tug, yaitu 0 ,M movie (B.7), le M (136), 10-5 M (B5) dan faktOr kedua adalah konsentrasi NAA yang terdiri dari 3 tare, yaitu 0 M (No), 10-7M (N7) dan Nel(N6).: Hasil penelitian menunjukkan bahwa kombinasi konsentrasi BAP dan NAA berpengaruh nyata terhadap jumlah tunas, panjang tunas dan jumlah daun pada sub kultur I dan sub kultur II.